The 988 suicide hotline—Lifeline or letdown? A pre-post policy analysis - Baker, Michaella; Sorensen, Juliet (Frontiers in Public Health, 2024)
Suicide has emerged as an urgent threat in recent years as COVID-19 impaired the health and economic wellbeing of millions of Americans. According to the Centers for Disease Control and Prevention, the impact of COVID-19 and the ongoing opioid epidemic has “taken a mental, emotional, physical, and economic toll on individuals, families, and communities,” increasing the need for innovative solutions to prevent suicide on a national scale. The National Suicide Hotline Designation Act of 2020 established 988 as the universal telephone number for suicide prevention and represents a key federal intervention to address this crisis. However, research on 9-8-8's effectiveness is limited, given the Act's recent enactment and implementation at the federal and state levels. This policy analysis investigates how and to what extent the mental health crisis system in Georgia has improved since the implementation of the 2020 Act as well as the implications of state law on population-level mental health outcomes. Georgia is used as a nationally representative case study for two reasons: (1) Georgia had a robust statewide suicide hotline prior to 2020, providing solid infrastructure on which federal expansion of a suicide hotline number could be built, and (2) the conflicting characteristics of Georgia's mental health system represent several different pockets of the U.S., allowing this analysis to apply to a broad range of states and locales. The paper draws on takeaways from Georgia to propose state and national policy recommendations for equitable interventions to prevent and respond to this form of violence.